2020
DOI: 10.1001/jama.2020.6637
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Screening at Illness Onset of Health Care Personnel With SARS-CoV-2 Infection in King County, Washington

Abstract: This study assessed the spectrum of initial symptoms at the onset of polymerase chain reaction–confirmed coronavirus disease 2019 (COVID-19) among health care personnel in King County, Washington.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
166
2
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(194 citation statements)
references
References 6 publications
(8 reference statements)
11
166
2
15
Order By: Relevance
“…27 In addition, subcontracted staff may have less access to paid sick leave -a critical element in allowing staff to self-isolate when ill. All of this is in line with evidence that staff are the main vectors of SARS-CoV-2 transmission in LTC facilities. [28][29][30] We are unaware of data that allow for comparisons of wages and rates of multisite employment between Ontario and British Columbia.…”
Section: Resultsmentioning
confidence: 99%
“…27 In addition, subcontracted staff may have less access to paid sick leave -a critical element in allowing staff to self-isolate when ill. All of this is in line with evidence that staff are the main vectors of SARS-CoV-2 transmission in LTC facilities. [28][29][30] We are unaware of data that allow for comparisons of wages and rates of multisite employment between Ontario and British Columbia.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of symptoms predictive of SARS-CoV-2 infection, single or in combination, is essential for the quest of screening guidance and in the recommendations of self-isolation to prevent further spread. In the large population-based study including 9282 HCW in the United States, 92% reported having at least one symptom among fever, cough and dyspnea 17 , and this symptom triad has been reported hallmark symptoms of COVID-19 infection [18][19][20] . Although fever was one of the most common Odds ratio of seropositivity to COVID-19 Odds ratio of seropositivity to COVID-19 symptoms among the seropositive HCW in this study, anosmia and ageusia were the symptoms most predictive of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Even with regular employee symptom screening, the use of face masks and other personal protective equipment, and other infection control measures, staff-to-resident transmission can occur while infected staff are asymptomatic or afebrile with mild symptoms that they fail to report. 5,6,10 Direct care staff also often work across multiple facilities, increasing the risk of cross-contamination. Many SNFs have implemented policies to limit staff working in more than one facility, but these policies could be further augmented by states offering financial support for hazard pay, paid sick leave, and other benefits to incentivize staff to limit movement outside their workplace.…”
Section: Discussionmentioning
confidence: 99%